Peran Kepemimpinan Kepala Sekolah, Disiplin Kerja, dan Komitmen dalam Meningkatkan Kinerja Guru di SMA Negeri 1 Takalar - Nasir Nasir (Majalah Ilmiah METHODA, 2025)
Improving the quality of education is inseparable from the role of teachers as the main implementers of the learning process. Optimal teacher performance is influenced by various factors, including the principal's leadership, work discipline, and teacher commitment. This study aims to reveal how these three factors contribute to improving teacher performance at SMA Negeri 1 Takalar. This study uses a qualitative approach with a descriptive method. Data was obtained through observation, in-depth interviews, and documentation. The subjects of the study were the principal and teachers at SMA Negeri 1 Takalar. The results of the study showed that school principals applied a participatory and communicative leadership style, thereby creating a conducive work environment and motivating teachers to work better. Teachers' work discipline can be seen from compliance with schedules, teaching readiness, and the implementation of orderly learning administration. Teachers' commitment is also high, reflected in their involvement in school activities and the enthusiasm for participating in professional training. These three factors support each other and significantly contribute to improving teacher performance. Thus, collaboration between the principal's leadership, discipline, and work commitment is an important foundation in creating a quality education system.